Developing an Integrated Ocean Observing System for New Zealand - O’Callaghan, Joanne; Stevens, Craig; Roughan, Moninya; Cornelisen, Chris; Sutton, Philip; Garrett, Sally; Giorli, Giacomo; Smith, Robert O.; Currie, Kim I.; Suanda, Sutara H.; Williams, Michael; Bowen, Melissa; et al. (Frontiers in Marine Science, 2019)
New Zealand (NZ) is an island nation with stewardship of an ocean twenty times larger than its land area. While the challenges facing NZ’s ocean are similar to other maritime countries, no coherent national plan exists that meets the needs of scientists, stakeholders or kaitiakitanga (guardianship) of NZ’s ocean in a changing climate. The NZ marine science community will use the OceanObs’19 white paper to establish a framework and implementation plan for a collaborative NZ ocean observing system (NZ-OOS). Co-production of ocean knowledge with Māori will be embedded in this national strategy for growing a sustainable, blue economy for NZ. The strengths of an observing system for a relatively small nation come from direct connections between the science impetus through to users and stakeholders of an NZ-OOS. The community will leverage off existing ocean observations to optimise effort and resources in a system that has historically made limited investment in ocean observing. The goal of the community paper will be achieved by bringing together oceanographers, data scientists and marine stakeholders to develop an NZ-OOS that provides best knowledge and tools to the sectors of society that use or are influenced by the ocean.